Efficacy and duration of analgesia with levobupivacaine combined with fentanyl or dexmedetomidine in lower extremity surgery: A meta-analysis - Mohit Gupta; Rana Pratap; Gajendra Pal Singh (Asian Journal of Medical Sciences)
Background: In combination with local anesthetics such as levobupivacaine, fentanyl, and dexmedetomidine improve post-operative analgesia after surgery on the lower extremities.